Policy options for modernizing the milling sector - Johnson, Michael E. (University of Pennsylvania Press, 2016)
The objective of this chapter is to assess the potential for transforming and modernizing the domestic rice milling sector in Nigeria using a mathematical programming model. More specifically, it seeks to address a number of key policy questions: Are there differential abilities and efficiencies among existing mill types (small to large) to supply the domestic market? Given the differences , what is the likely path for transforming the sector into a modernized agro-indusrry in order to better compete with imports and meet domestic demand? What would be the welfare implications, especially for rural employment? To answer these questions, a survey of the literature, field data, and use of a spatial equilibrium rice milling model were adopted.